The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.2147/ppa.s110167
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pharmacist-managed clinic on medication adherence and health-related quality of life in patients with COPD: a randomized controlled study

Abstract: IntroductionCOPD is rapidly becoming one of the most challenging health problems worldwide, which is characterized by not fully reversible airflow limitation. Although a lot of treatment medications have been delivered, the treatment goals of COPD are often not achieved. Furthermore, few well-designed randomized controlled trials in the People’s Republic of China have been reported to evaluate the impact of pharmacist-managed clinic (PMC) on medication adherence and health-related quality of life in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(87 citation statements)
references
References 22 publications
(19 reference statements)
2
83
0
2
Order By: Relevance
“…A prospective randomised controlled trial assessed the impact of pharmacist-managed clinic (similar to the HMMR service) on medication adherence in COPD patients. [27] The Table 3 Changes in the medication nonadherence frequencies as a result of intervention n (%) in both study groups study showed a significantly greater improvement in medication adherence compared with baseline and to the control group, which was still found after 12 months, attributed to the service received from the clinical pharmacist. [27] Many strategies are found to improve patient's adherence.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…A prospective randomised controlled trial assessed the impact of pharmacist-managed clinic (similar to the HMMR service) on medication adherence in COPD patients. [27] The Table 3 Changes in the medication nonadherence frequencies as a result of intervention n (%) in both study groups study showed a significantly greater improvement in medication adherence compared with baseline and to the control group, which was still found after 12 months, attributed to the service received from the clinical pharmacist. [27] Many strategies are found to improve patient's adherence.…”
Section: Discussionmentioning
confidence: 91%
“…[27] The Table 3 Changes in the medication nonadherence frequencies as a result of intervention n (%) in both study groups study showed a significantly greater improvement in medication adherence compared with baseline and to the control group, which was still found after 12 months, attributed to the service received from the clinical pharmacist. [27] Many strategies are found to improve patient's adherence. Providing patient home visits is an important strategy required by some patients for adherence to be optimised.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The reasons for exclusion were as follows: not asthma or COPD patients, not a RCT, not pharmacist-led, no usual care control group, no outcome of interest and others. We included 13 studies 29-41 , 10 studies [29][30][31][33][34][35][36][37]40,41 reported medication adherence, 3 studies 30,33,34 could not be included in quantitative analysis because of the lack of available original data; 7 studies [31][32][33][34][38][39][40] reported inhalation technique, 3 studies 33,38,39 could not be included in quantitative analysis because of the lack of dichotomous data. The process of article selection is presented in Figure 1.…”
Section: Included Studies and Study Characteristicsmentioning
confidence: 99%
“…It is the second most common reason for emergency hospital admission.According to WHO, COPD has become the fourth leading cause of mortality in the US. It is estimated to become the fifth leading cause of disease burden in 2020 [128]. In 2015 alone, the death toll due to asthma was 383,000 globally [129].…”
Section: Asthma and Copd Managementmentioning
confidence: 99%